The Domino Effects of Federal Research Funding. - Lauren Lanahan; Alexandra Graddy-Reed; Maryann P Feldman (PLoS ONE, 2016)
The extent to which federal investment in research crowds out or decreases incentives for investment from other funding sources remains an open question. Scholarship on research funding has focused on the relationship between federal and industry or, more comprehensively, non-federal funding without disentangling the other sources of research support that include nonprofit organizations and state and local governments. This paper extends our understanding of academic research support by considering the relationships between federal and non-federal funding sources provided by the National Science Foundation Higher Education Research and Development Survey. We examine whether federal research investment serves as a complement or substitute for state and local government, nonprofit, and industry research investment using the population of research-active academic science fields at U.S. doctoral granting institutions. We use a system of two equations that instruments with prior levels of both federal and non-federal funding sources and accounts for time-invariant academic institution-field effects through first differencing. We estimate that a 1% increase in federal research funding is associated with a 0.411% increase in nonprofit research funding, a 0.217% increase in state and local research funding, and a 0.468% increase in industry research funding, respectively. Results indicate that federal funding plays a fundamental role in inducing complementary investments from other funding sources, with impacts varying across academic division, research capacity, and institutional control.